Genome resources for climate‐resilient cowpea, an essential crop for food security. (3rd February 2017) - Muñoz‐Amatriaín, María; Mirebrahim, Hamid; Xu, Pei; Wanamaker, Steve I.; Luo, MingCheng; Alhakami, Hind; Alpert, Matthew; Atokple, Ibrahim; Batieno, Benoit J.; Boukar, Ousmane; Bozdag, Serdar; Cisse, Ndiaga; et al.
Summary: Cowpea ( Vigna unguiculata L. Walp.) is a legume crop that is resilient to hot and drought‐prone climates, and a primary source of protein in sub‐Saharan Africa and other parts of the developing world. However, genome resources for cowpea have lagged behind most other major crops. Here we describe foundational genome resources and their application to the analysis of germplasm currently in use in West African breeding programs. Resources developed from the African cultivar IT97K‐499‐35 include a whole‐genome shotgun (WGS) assembly, a bacterial artificial chromosome (BAC) physical map, and assembled sequences from 4355 BACs. These resources and WGS sequences of an additional 36 diverse cowpea accessions supported the development of a genotyping assay for 51 128 SNPs, which was then applied to five bi‐parental RIL populations to produce a consensus genetic map containing 37 372 SNPs. This genetic map enabled the anchoring of 100 Mb of WGS and 420 Mb of BAC sequences, an exploration of genetic diversity along each linkage group, and clarification of macrosynteny between cowpea and common bean. The SNP assay enabled a diversity analysis of materials from West African breeding programs. Two major subpopulations exist within those materials, one of which has significant parentage from South and East Africa and more diversity. There are genomic regions of high differentiation between subpopulations, one of which coincides with a cluster of nodulin genes. The new resources and knowledge help to define goals and accelerate the breeding of improved varieties to address food security issues related to limited‐input small‐holder farming and climate stress. Significance Statement: Cowpea, also known as black‐eyed pea, is a major crop for global food security but lacks genomic resources available for other major crop plants. Here we present publicly available genome resources including annotated genomic sequences, a physical map, a high‐density genotyping array, and a sequence‐enriched consensus genetic map. We have used these resources to assess the genetic diversity of cowpeas from West African breeding programs and to clarify synteny between cowpea and common bean.